Switching from Deferasirox Dispersible Tablets to Deferasirox Film-Coated Tablets: Is There an Effect on Ferritin Levels in Children and Adolescents with Transfusion-Dependent Anemia? - Esra Arslantaş; Ali Ayçiçek; Sibel Akpınar Tekgündüz; Duygu Özkorucu Yıldırgan; Ayşe Özkan Karagenç; Tuba Nur Tahtakesen Güçer; Ayşe Gonca Kaçar; Cengiz Bayram; Nihal Özdemir (Turkish Archives of Pediatrics)
Objective: To investigate the effect of switching from deferasirox dispersible tablet (DT) to deferasirox film-coated tablet (FCT) on serum ferritin (SF) levels in transfusion-dependent patients.